Pengaruh Kepercayaa dan Kemudahan Penggunaan Aplikasi Marketplace Terhadap Adopsi E-Commerce dan Profitabilitas Pada Bisnis Kuliner Di kota Banjarmasin - Ainun Mardhiah; Suyatno (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: The COVID-19 pandemic has had a very big impact, one of which is on culinary business actors in the city of Banjarmasin who experienced a decline in sales so they chose to close their businesses, to increase the enthusiasm of the economy, business actors are required to innovate in the sales system, one of which is by adopting e- commerce. This type of research uses a descriptive quantitative approach with an explanatory research type, there are 163 respondents, namely small business actors in the culinary business in the city of Banjarmasin. The data analysis uses the SPSS version 24 application. The results of the analysis show that market trust and ease of use have a significant effect on e-commerce adoption, and e-commerce adoption has a significant effect on profitability. However, trust and ease of use of marketplace applications do not significantly affect profitability. The adoption of e-commerce mediation has a significant effect of trust on profitability and adoption of e-commerce does not have a significant mediating effect on the ease of use of market applications on the profitability of small culinary businesses in the city of Banjarmasin